2010
DOI: 10.1007/s11274-010-0536-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mannitol producing strains of Leuconostoc species

Abstract: Mannitol is a naturally occurring low calorie sweetener, widely used in the food, pharmaceutical, medicine and chemical industries. In this study mannitol producing strains of Leuconostoc spp. (210) were isolated from a wide array of sources such as raw milk, fermented milks, fermented cereal foods, fruits, vegetables and sugar factory syrup. During initial screening, half of the population of these isolates (105) exhibited ability to produce mannitol to a variable extent. Only 11.4% isolate produced mannitol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…consequently, it could be assumed that the studied strains are mannitol + . our preliminary results are in agreement with those of Kim et al (17) and Patra et al (33). it could be hypothesized that our strains have the potential to be used in further studies dealing with the production of fructans and mannitol.…”
Section: Polymer Characterizationsupporting
confidence: 93%
See 1 more Smart Citation
“…consequently, it could be assumed that the studied strains are mannitol + . our preliminary results are in agreement with those of Kim et al (17) and Patra et al (33). it could be hypothesized that our strains have the potential to be used in further studies dealing with the production of fructans and mannitol.…”
Section: Polymer Characterizationsupporting
confidence: 93%
“…Four of these strains produced FS of approximately 130 kDa in medium with or without sucrose (44). Several heterofermentative lAB belonging to the genera Lactobacillus and Leuconostoc have been studied for production of mannitol from fructose and sucrose (33,41). For heterofermentative lAB, fructose acts as an electron acceptor for regeneration of nAD + and such strains contain nAD(P)h mannitol dehydrogenase (MDh) (49).…”
Section: Polymer Characterizationmentioning
confidence: 99%
“…Saha and Nakamura (2003) reported on the ability to produce mannitol from fructose by strains of Lactobacillus brevis, Lactobacillus buchneri, Lactobacillus cellobiosus, Lactobacillus fermentum, Lactobacillus intermedius, Leuconostoc amelibiosum, Leuconostoc citrovorum, Leuconostoc mesenteroides and Leuconostoc paramesenteroides. Recently, Patra et al (2011) characterized different mannitol-producing strains of Leuconostoc isolated from a broad range of raw and indigenous fermented foods. The strain L. intermedius NRRL B-3693 selected by Saha and Nakamura (2003) was able to produce up to 198 g/l of mannitol from a high fructose concentration (300 g/l) medium.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis additionally showed that the community of Lactobacillales is dominated by Leuconostoc species, presumably due to the low percentage of salt added in the cover brine (2%). Species of Leuconostoc are commonly found in fruits and vegetables and they play important roles in the fermentation of dairy products, vegetables and meats given their ability to ferment sugars (sucrose, glucose, fructose) producing lactic acid, glucans, fructans, and mannitol (Groben et al, 2001; Kim et al, 2002; Patra et al, 2011). …”
Section: Resultsmentioning
confidence: 99%